Combination of geodetic observations and models for glacial isostatic adjustment fields in Fennoscandia - Hill, Emma M.; Davis, James L.; Tamisiea, Mark E.; Lidberg, Martin (Journal of Geophysical Research, 2010)
We demonstrate a new technique for using geodetic data to update a priori predictionsfor Glacial Isostatic Adjustment (GIA) in the Fennoscandia region. Global PositioningSystem (GPS), tide gauge, and Gravity Recovery and Climate Experiment (GRACE)gravity rates are assimilated into our model. The technique allows us to investigate theindividual contributions from these data sets to the output GIA model in a self‐consistentmanner. Another benefit of the technique is that we are able to estimate uncertaintiesfor the output model. These are reduced with each data set assimilated. Any uncertaintiesin the GPS reference frame are absorbed by reference frame adjustments that are estimatedas part of the assimilation. Our updated model shows a spatial pattern and magnitudeof peak uplift that is consistent with previous models, but our location of peak upliftis slightly to the east of many of these. We also simultaneously estimate a spatiallyaveraged rate of local sea level rise. This regional rate (∼1.5 mm/yr) is consistent forall solutions, regardless of which data sets are assimilated or the magnitude of a priori GPSreference frame constraints. However, this is only the case if a uniform regional gravityrate, probably representing errors in, or unmodeled contributions to, the low‐degreeharmonic terms from GRACE, is also estimated for the assimilated GRACE data. Ourestimated sea level rate is consistent with estimates obtained using a more traditionalapproach of direct “correction” using collocated GPS and tide gauge sites.